The Effect of Physical Evidence, Responsiveness, and Assurance on Customer Purchasing Decisions at PT. Asuransi Reliance - M. Rinanda Hidayat; Gilbert Leandro; Herlina Novita; Harun Lubis (GoAcademica Research & Publishing, 2023)
In modern times, the need for transportation is very high, this is indicated by the large number of people who have their vehicles. As the number of private vehicles increases, the possibility of traffic accidents occurs, the solution to deal with this problem is: utilizing vehicle insurance services. PT. Asuransi Reliance is a car insurance company that is committed to being the best choice in the vehicle insurance industry. In the preparation of this thesis, the main thing discussed is the effect of responsiveness, guarantees, and physical evidence on customer purchasing decisions on PT. Asuransi Reliance. In this study, the author used an interview method that focuses on primary data as a data source. Based on the findings of this study, the author concludes that physical evidence, responsiveness, and guarantees influence the purchase decision of PT. Asuransi Reliance, where the better physical evidence, responsiveness, and guarantees are owned by PT. Asuransi Reliance then the higher the level of customer purchase decisions. From the conclusions and results of the analysis in the discussion chapter, the author would like to provide suggestions, namely: the company PT. Asuransi Reliance needs to improve the quality of their company's physical evidence, responsiveness, and assurance to improve purchasing decisions.